Changing treatments paradigms and role of immunotherapy in recurrent endometrial cancer. Issue 1 (February 2022) - Chelariu-Raicu, Anca; Mahdi, Haider; Slomovitz, Brian M.
Abstract : Purpose of review: Over the past decade, the treatment of patients diagnosed with endometrial cancer (EC) shifted away from the use of chemotherapy to more novel targeted therapy and immunotherapy approaches. Recent findings: The Cancer Genome Atlas data demonstrated different subgroups within ECs, more specifically, it facilitated the identification of predictive biomarkers. In particular, immunotherapies (immuno-oncology (IO)) are active either as monotherapy or in combination with other agents, depending on the biomarker profile of the tumor. Summary: In May 2017, pembrolizumab was approved for patients with microsatellite instability high (MSI-H) EC. More recently, this approval was extended for patients harvesting tumors with a high tumor mutational burden status. Furthermore, in July 2021, the combination of pembrolizumab and lenvatinib was approved for patients who do not exhibit MSI-H disease. Given the wealth of targets in EC and different targetable mutations, the challenge will be to choose the proper treatment and the proper sequencing to derive the best outcome in the first-line setting and improve outcomes in subsequent settings. This review summarizes the current indications of immunotherapy for the treatment of advanced and recurrent EC. We outline the role of testing for uterine cancer and its implication in therapy management. Finally, we address new concepts for immunotherapy combinations with other therapies.